1994
DOI: 10.1136/adc.70.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of chronic suppurative lung disease.

Abstract: Forty one (1%) of 4000 children referred for respiratory disease had chronic suppurative lung disease not due to cystic fibrosis. Further investigations showed congenital malformations in six (15%), primary ciliary dyskinesia syndrome in seven (17%), 11 had immunological abnormalities (27%), and two bronchiectasis due to aspiration (5°/0). Therefore the underlying cause for the disease was found in 63%. Identification of predisposing causes may facilitate prevention of further bronchial damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 6 publications
1
56
0
4
Order By: Relevance
“…It is difficult to know whether these subjects had severe or repeated episodes of respiratory sepsis leading to permanent bronchial damage that were not recalled, or whether they had an unidentified intrinsic impairment to host defence that [19] reviewed 41 cases of bronchiectasis who presented with chronic productive cough, and no cause was found in 37% of their study group. Forty-eight per cent of studied subjects from a New Zealand cohort, despite extensive investigations, had no known cause for their bronchiectasis [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to know whether these subjects had severe or repeated episodes of respiratory sepsis leading to permanent bronchial damage that were not recalled, or whether they had an unidentified intrinsic impairment to host defence that [19] reviewed 41 cases of bronchiectasis who presented with chronic productive cough, and no cause was found in 37% of their study group. Forty-eight per cent of studied subjects from a New Zealand cohort, despite extensive investigations, had no known cause for their bronchiectasis [20].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of bronchiectasis in other rare PIDs such as hyper-IgE syndrome (<2.5% in children and very rare in adults) [74,84,85], phagocyte defects (<1%-10% in children and <1% in adults) [86,87], and transporter antigen peptide deficiency (rare in children and very rare in adults) [87,88] is low. The microorganisms associated with bronchiectasis in patients with PID are shown in the Table. High-resolution computed tomography (HRCT) is considered a reliable test for assessing bronchiectasis in patients with PID [89][90][91].…”
Section: Bronchiectasismentioning
confidence: 99%
“…Postinfectious bronchiectasis in the normal host is becoming distinctly uncommon, and, in developed countries, most patients with the disorder have an underlying systemic illness. An underlying cause of the disease was identified in 40–63% of patients in different studies [3,4,5]. Several studies reported a higher incidence of non-CF bronchiectasis in different minority groups, which was thought to be related to low socioeconomic status [6,7,8].…”
Section: Introductionmentioning
confidence: 99%